Comparative efficacy testing — Fractional flow reserve by coronary computed tomography for the evaluation of patients with stable chest pain. (15th March 2015) - Rajani, Ronak; Webb, Jessica; Marciniak, Anna; Preston, Rebecca
Abstract: Background: To evaluate diagnostic strategies in a rapid access chest pain clinic (RACPC) in the United Kingdom and to predict the economical and clinical impacts of incorporating fractional flow reserve by coronary computed tomographic angiography (FFRCT ) into future pathways. Methods: A retrospective analysis of consecutive patients referred to a RACPC in the United Kingdom. All patients had an evaluation of cardiovascular risk factors and symptoms from which the pre-test likelihood (PTL) of coronary artery disease (CAD) was evaluated using the Diamond Forrester (DF) criteria. All investigative strategies and their results were recorded. For the FFRCT economic evaluation of 1000 patients, standard National Health Service Tariffs were then applied and compared with a strategy that utilised FFRCT for varying PTL categories. Results: There were 410 patients with a median age of 57 (31–85) years. The DF criteria classified 39 (9.5%) patients as having a PTL of < 10%, 76 (18.5%) 10–29% PTL, 117 (28.5%) 30–60% PTL, 114 (27.8%) 60–90% PTL and 64 (15.6%) > 90% PTL. The concordance with the NICE recommended guidelines was < 50% with the prevalence of obstructive CAD being < 5% in patients with a PTL < 90%. A model utilising FFRCT for patients with a PTL 10–90% predicted a 48% and 49% reduction in invasive angiography and percutaneous coronary intervention, a saving of £200 per patient and a reduction in relative adverse event rates of 4%. Conclusions: The DF algorithm overestimates the PTL of CAD supporting an extended role for coronary CTA. Strategies incorporating FFRCT may confer benefits in evaluating patients with stable chest pain. Highlights: There is considerable heterogeneity in the evaluation of patients with stable chest pain in the UK. Clinicians demonstrate a preference for clinical judgement over national guidelines. Established risk-scoring algorithms overpredict the rates of obstructive coronary disease. Novel strategies incorporating FFRCT offer substantial potential in refining patient pathways. FFRCT is likely to reduce rates of invasive procedures, cost and event rates.